2013
DOI: 10.1093/nar/gkt1310
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the regulatory function of a complex zinc-binding domain in a replicative arterivirus helicase resembling a nonsense-mediated mRNA decay helicase

Abstract: All positive-stranded RNA viruses with genomes >∼7 kb encode helicases, which generally are poorly characterized. The core of the nidovirus superfamily 1 helicase (HEL1) is associated with a unique N-terminal zinc-binding domain (ZBD) that was previously implicated in helicase regulation, genome replication and subgenomic mRNA synthesis. The high-resolution structure of the arterivirus helicase (nsp10), alone and in complex with a polynucleotide substrate, now provides first insights into the structural basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
98
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(105 citation statements)
references
References 61 publications
(126 reference statements)
6
98
1
Order By: Relevance
“…Zn3 is the most distantly located zinc from the helicase core (6.4Å away from Zn2; Fig 1A), and the ZBD/CH is tightly attached to the helicase core in CoV nsp13, it is therefore unsurprising that the impaired binding of Zn3 has the minimal effect on the enzymatic activity of nsp13[32]. This hypothesis is supported by the mutagenesis study of EAV nsp10[25,32], which also showed that while mutant H2414A (ligand for Zn3) retained residual ATPase/ helicase activity and wild-type-level nucleic acid binding activity, the activities of mutants C2395A (ligand for Zn1) and H2399A (ligand for Zn2) was completely abolished.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Zn3 is the most distantly located zinc from the helicase core (6.4Å away from Zn2; Fig 1A), and the ZBD/CH is tightly attached to the helicase core in CoV nsp13, it is therefore unsurprising that the impaired binding of Zn3 has the minimal effect on the enzymatic activity of nsp13[32]. This hypothesis is supported by the mutagenesis study of EAV nsp10[25,32], which also showed that while mutant H2414A (ligand for Zn3) retained residual ATPase/ helicase activity and wild-type-level nucleic acid binding activity, the activities of mutants C2395A (ligand for Zn1) and H2399A (ligand for Zn2) was completely abolished.…”
Section: Discussionmentioning
confidence: 84%
“…Nidovirus helicases share many structural features with the eukaryotic Upf1 helicase, a key factor in nonsense-mediated mRNA decay in cells[24,25]. Upf1 is a multi-domain protein comprising of an N-terminal Cys-His-rich domain (CH domain) coordinating three zinc atoms, a 1B domain with the β-barrel fold and a conserved SF1 helicase core with a 1C insert in the first RecA-like domain[24,26].…”
Section: Introductionmentioning
confidence: 99%
“…We found that only mutations at Cys25 and His32 impaired the binding and unwinding abilities, whilst the others had no obvious influence on the biochemical activities of PRRSV nsp10. The EAV nsp10 crystal structure shows that 12 Cys or His residues participate in ZBD formation and bind to three zinc ions (Deng et al, 2014). Our results demonstrated that some of these sites are not required for the function of ZBD, but Cys25 and His32 may be critical for forming or maintaining the conformation of ZBD of PRRSV nsp10.…”
mentioning
confidence: 76%
“…A high-resolution structure of the EAV helicase binding to a ssDNA substrate is now available. The nsp10 of EAV appears to be structurally similar to mRNA decay factor Upf1, suggesting that nsp10 plays a role in the post-transcriptional quality control of large viral RNA genomes (Deng et al, 2014).…”
mentioning
confidence: 99%
“…Panel D is adapted from Deng et al (2014). numerous related proteins, whose number has steadily increased along with genomics projects. The helicase SFs are distinguished by characteristic conserved sequences (motifs) that are often used to identify new members.…”
mentioning
confidence: 99%